Vestibular myogenic and acoustical brainstem evoked potentials in neurological practice - O. S. Korepina; N. S. Alekseeva; V. V. Gnezditskiy (Нервно-мышечные болезни)
Along with the inspection of acoustical cortex and brainstem EP in neurologic, otoneurologic and audiologic practice recently start to use so-called vestibular evoked myogenic potentials (VEMP). It is shown, that at ear stimulation by a loud sound and record of sterno-cleidomastoid contraction is possible to estimate function of the inferior vestibular nerve and vestibulospinal pathways, a sacculo-cervical reflex. In article some methodical and clinical questions of application of these kinds are presented. Combine research acoustic brainstem EP and VEMP allows to confirm effectively lesions of acoustical and vestibular ways at brainstem. The conclusion becomes, that this kind of inspection is important for revealing demielinisation and defeats in vestibulospinal tract, that quite often happens at MS, and at estimation of efficiency of treatment